Between Pleasure and Pain: A Pilot Study on the Biological Mechanisms Associated with BDSM Interactions in Dominants and Submissives. Issue 4 (7th February 2020) - Wuyts, Elise; De Neef, Nele; Coppens, Violette; Fransen, Erik; Schellens, Eline; Van Der Pol, Maarten; Morrens, Manuel
Abstract: Background: BDSM is an abbreviation used to reference the concepts of bondage and discipline, dominance and submission, sadism, and masochism, enacted by power exchanges between consensual partners. Aim: To shed light upon the rewarding biological mechanisms associated with BDSM interactions. Methods: A group of 35 BDSM couples (dominant and submissive counterparts) were recruited and tested during a BDSM interaction, with an additional control group of 27 non-BDSM interested people tested in a normal social interaction. Outcomes: We compared the evolution of the stress and reward hormone levels of cortisol, beta-endorphins, and endocannabinoids (2AG and anandamide) in a group of BDSM practitioners before and after an active BDSM interaction with the levels in control individuals. Results: We showed that submissives showed increases in cortisol and endocannabinoid levels due to the BDSM interaction, with dominants only showing increased endocannabinoid levels when the BDSM interaction was associated with power play. Clinical Implications: This study effectively provides a link between behavior that many think of as aberrant on one hand, and biological pleasure experience on the other, in the hope that it may relieve some of the stigma these practitioners still endure. Strengths & Limitations: It is one of the first and largest studies of its kind, but is still limited in sample size and only represents a specific population of Flemish BDSM practitioners. Conclusion: Even though this is one of the first studies of its kind, we can conclude that there is a clear indication for increased pleasure in submissives when looking at biological effects of a BDSM interaction, which was related to the increases in experienced stress.